Etika interaksi antara konselor dan klien ditinjau dari hadis nabawi - Damayanti, Riska; Maturidi, Maturidi; Asmadin, Asmadin; Yani, Reda (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
Ethics plays an important role and becomes a guideline for human behavior. This is also the case with counselors who must have interaction ethics in counseling services. Specialized research discusses more specific prophetic interaction ethics, namely some that I would like to investigate prophetic in hadith. The purpose of this study is to explore how hadith relates to counselor-client relationship ethics and how the practice of Prophetic hadith relates to relationship ethics in counselor-client relationship ethics. This research uses a qualitative approach with descriptive analysis techniques to describe the topic and subject of the research. The data sources used are primary data, secondary data from hadith books, and books related to the research focus. The findings of this study are relevant to the ethics of counselor-client interaction, namely: The counselor must be polite, greeting, humble, share the good news, behave well, be honest, patient, empathetic, shameful, obey prohibitions, and hurt. as exemplified by the Prophet Muhammad. The conclusion that can be drawn is that in order for the counseling process to run effectively, counselors must master and understand the ethics of interaction in the counseling process.